2003
DOI: 10.2214/ajr.180.4.1800901
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of the Ipsilateral Breast in Women with Percutaneously Proven Breast Cancer

Abstract: MR imaging identified additional sites of ipsilateral cancer in 27% of women with percutaneously proven breast cancer. The yield was highest in women with a family history of breast cancer or infiltrating lobular histology in the index cancer. Change after biopsy was infrequent and did not interfere with the MR imaging interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
145
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 348 publications
(165 citation statements)
references
References 38 publications
15
145
1
4
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15] Of the 22 malignant lesions identified only on DCE MRI, 13 (59%) lesions were invasive carcinoma and 5 (56%) lesions of the 9 DCE MRIdetected ductal carcinomas in situ were grade 3, with 1 lesion being 8 cm in size. These clinically significant lesions would have been missed if pre-operative DCE MRI had not been performed, lending some support for breast MRI in staging newly diagnosed breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13][14][15] Of the 22 malignant lesions identified only on DCE MRI, 13 (59%) lesions were invasive carcinoma and 5 (56%) lesions of the 9 DCE MRIdetected ductal carcinomas in situ were grade 3, with 1 lesion being 8 cm in size. These clinically significant lesions would have been missed if pre-operative DCE MRI had not been performed, lending some support for breast MRI in staging newly diagnosed breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3 Numerous studies have also shown that MRI improves the detection of occult tumour foci in the ipsilateral and contralateral breasts in patients with newly diagnosed breast cancer, leading to changes in surgical planning. [4][5][6][7][8][9][10][11][12][13][14][15] Systematic reviews of the literature found that pre-operative MRI detected additional ipsilateral disease in 16-20% of patients and occult synchronous contralateral cancer in 4-5% of patients. [16][17][18] Despite the widespread use of breast MRI for pre-operative staging in recent years, this use remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Indications for an MRI examination included preoperative evaluation before planned breast conserving operation to exclude multicentricity and bilaterality, assessment of axillary lymph node status, and evaluation of residual tumor after excisional biopsy at other hospitals. We defined additional lesions on MRI according to the definition of Liberman et al (12). MRI lesions were considered as a separate entity if they were located in a different breast quadrant than the index cancer, if they were in the same quadrant but separated from the index cancer by at least 1.0 cm of intervening normal-appearing tissue on MRI, or if they were in the same quadrant and contiguous with the index cancer but extended at least 4.0 cm beyond the site of the index cancer.…”
Section: Patient Selection and Data Collectionmentioning
confidence: 99%
“…However, MRI has higher sensitivity than X-ray mammography in identifying occult breast lesions, particularly dense lesions (11). MRI can provide a more reliable basis for accurate staging and the development of a clinical treatment strategy for breast cancer.…”
Section: Introductionmentioning
confidence: 99%